ANALISIS PERTUMBUHAN SEKTOR PERBANKAN DI INDONESIA TAHUN 2001-2008 - . Asmirawati (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2010)
Intention of this research is to know level of growth of banking credit in Indonesia and know macro variable influence that is resident amounts, earnings of perkapita and amount of money supplies to growth of banking credit. Analyzer applied to know resident growth influence, income percapita, amount of money supplies to growth of credit is doubled linear regression test with statistical test two directions that is T test and F test and test ekonometrika that is classic assumption test (multikolinierity test, heteroskedastisity test, autocorrelation test). Result of research at doubled linear regression shows growth of number of residents to growth of credit influential significant. while earnings growth of percapita doesn't have an effect on significant to growth of credit and growth of amount of money supplies influential significant to growth of credit. Based on conclusion to macro variable of chartered investment counsel can be cought up with growth of credit as according to ability of Negara to be realized secure and prosperous public.